S&T Policy-making - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
This dossier is intended to enable the ACP community of scientists, policy makers and other stakeholders in the agricultural and related sectors and disciplines to share their knowledge and experiences in order to enhance national and regional policy dial